Efficient lipase purification using reverse micellar extraction - Gaikaiwari, Raghavendra P.; Wagh, Shilpa A.; Kulkarni, Bhaskar D. (Bioresource Technology, 2012)
Reverse micellar extraction (RME) of enzyme provides an attractive option for conventional method with the potential to achieve purification and concentration in a single step with high yield. This study presents a methodology for optimization of RME with Pseudomonas lipase as model system. Fold-purification, percent recovery and extraction time were the objective functions while the type and concentration of surfactant, contact time, pH, ionic strength, and the ratio of organic to aqueous phase were the decision variables. Under optimized conditions, the AOT (Aerosol OT (bis 2-ethylhexyl) sodium sulfosuccinate)-isooctane system gave a 15-fold purification, 80% recovery and 2.5-fold concentration of the Pseudomonas lipase with process time of 45 min. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: (Hexadicetyltrimethylammoniumbromide); AOT; CTAB; Lipase; RME

Extraction and purification of tannase by reverse micelle system - Gaikaiwari, Raghavendra P.; Wagh, Shilpa A.; Kulkarni, Bhaskar D. (Separation and Purification Technology, 2012)
Tannin acyl hydrolase commonly called as tannase (EC 3.1.1.20) is a commercially important enzyme. Partially purified and concentrated tannase is required for commercial applications. Typical objectives of purification process comprise high fold-purification, recovery and concentration. These objectives may be potentially conflicting. Conventional methods of purification require multiple steps which are time consuming and may cause higher loss. Reverse micellar extraction (RME) using ionic surfactants provides an attractive option for concentration and purification of tannase which is a highly hydrophilic glycoprotein. This study presents an optimized methodology for RME and purification of Aspergillus allahabadi intracellular tannase. Fold-purification, percent recovery and extraction time were the objective while the type and concentration of surfactant, contact time, pH, ionic strength, and the ratio of organic to aqueous phase were the decision variables. Some of these parameters were also studied for their effect on back-extraction. Among the surfactants tested, CTAB-isooctane system was found to be suitable. Under optimized conditions, 12.7-fold purification, 81.2% recovery and 3-fold concentration of tannase with a process time of 45 min was obtained. Conventional purification methods provided a higher fold-purification albeit at a much lower enzyme recovery. Further, the conventional method requires a process time of several hours. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: CTAB; Reverse micellar extraction; Tannase